Kepatuhan Pelaku Usaha Mikro Kecil Menengah Terhadap Standar Kesehatan Pangan Melalui Perizinan Produk Industri Rumah Tangga (Studi Kasus di Dinas Kesehatan Kabupaten Lombok Timur) : Compliance Of Micro Medium Enterprises Against Food Health Standards Through Licensing Of Household Industry Products (Case Study In East Lombok Regency Health Office) - SILVIA AYU ROSWIANA (Fakultas Hukum Universitas Gunung Rinjani, 2023)
This research is motivated by the large number of food industries in Indonesia, especially in East Lombok. With the production activities of various types of processed food, this creates a responsibility for business actors or UMKM which must be fulfilled by registering PIRT permits for their food products. The focus of this research refers to the benefits that home-scale UMKM get from permits issued by the health service, then what sanctions are given if business actors who have permits commit irregularities. The data collection technique uses interview techniques and documentation regarding matters related to research. And the research results show that the benefits greatly influence the impact of food production on UMKM who can officially and legally market their products in modern markets. Provide sanctions in accordance with deviations committed by business actors if they are proven to have committed violations against the food products they process and it is the responsibility of all business actors to provide a sense of security to consumers.